Decontamination of fresh and minimally processed produce - Gomez-Lopez, Vicente M. (Ames, Iowa : Wiley-Blackwell, 2012)
Attempts to provide safer and higher quality fresh and minimally processed produce have given rise to a wide variety of decontamination methods, each of which have been extensively researched in recent years. Decontamination of Fresh and MinimallyProcessed Produce is the first book to provide a systematic view of the different types of decontaminants for fresh and minimally processed produce. By describing the different effects - microbiological, sensory, nutritional and toxicological
1. Produce contamination -- 2. Decontaminants -- 3. Biological decontamination strategies -- 4. Physical methods -- 5. Storage strategies -- 6. Modeling tools
Includes bibliographical references and index
Keywords: Food industry and trade -- Production control; Food industry and trade -- Sanitation; Food -- Safety measures